2013
DOI: 10.4067/s0718-58392013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed and feeding on the carcass characteristics of the Chilote breed lamb

Abstract: The Chilote sheep has been developed in an isolated environment, based on grazing lands with low nutritive value belonging to small-scale producers, because of which there is little information about the use of this breed for meat production. The objective of this work was to determine the effects on lamb carcasses of two breeds with different productive purposes and fed on pastures with different nutritional quality. Three groups of lambs were used. The first and second groups were composed of 13 and 11 Chilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…Slaughter weight (42.7 -44.5 kg), hot carcass weight (19.7 -20.7 kg), and cold carcass weight (19.1 -20.1 kg) varied considerably, whereas, cold carcass yield (44.5 -46.6 %) and chilling loss (2.2 -3.1 %) were corroborated by earlier studies (Greer and Jones 1997;Carrasco et al 2009;Suliman et al 2021;Silva et al 2021;Atsbha et al 2021). Ramírez-Retamal et al (2013) found that carcasses with smaller D values but more F value showed the highest compactness which is in line with the results of earlier studies (Carrasco et al 2009;Diaz et al 2002). Most of the studies have reported that the first quality of commercial meat cuts represents more than 60 % of the carcass weight (Caneque et The inverse relationship between WHC and CL observed in this study was supported by earlier studies as well (Rubiano et al 2009;Venturini et al 2020).…”
Section: Discussionsupporting
confidence: 78%
“…Slaughter weight (42.7 -44.5 kg), hot carcass weight (19.7 -20.7 kg), and cold carcass weight (19.1 -20.1 kg) varied considerably, whereas, cold carcass yield (44.5 -46.6 %) and chilling loss (2.2 -3.1 %) were corroborated by earlier studies (Greer and Jones 1997;Carrasco et al 2009;Suliman et al 2021;Silva et al 2021;Atsbha et al 2021). Ramírez-Retamal et al (2013) found that carcasses with smaller D values but more F value showed the highest compactness which is in line with the results of earlier studies (Carrasco et al 2009;Diaz et al 2002). Most of the studies have reported that the first quality of commercial meat cuts represents more than 60 % of the carcass weight (Caneque et The inverse relationship between WHC and CL observed in this study was supported by earlier studies as well (Rubiano et al 2009;Venturini et al 2020).…”
Section: Discussionsupporting
confidence: 78%
“…But it was higher than those reported by Ugur et al (2013) in Karayaka female lambs and Júnior et al (2013) in Santa Inês lambs. Results of the current investigation indicated the overall mean of animal loin weight was lower than that of Suffolk (3.68±0.98 kg, Ramírez-Retamal et al 2013). The type of barley effect on loin weight was not significant.…”
Section: Resultscontrasting
confidence: 57%
“…Feeding white barley showed higher (P<0.05) weights of some carcass parts including leg, shoulder, breast, fore shank, and flank (Table 5). The Results revealed that overall mean of lamb leg weight was lower than that indicated by Ramírez-Retamal et al (2013) in Chilote sheep. But it was higher than those reported by Ugur et al (2013) in Karayaka female lambs and Júnior et al (2013) in Santa Inês lambs.…”
Section: Resultsmentioning
confidence: 65%
“…Ramírez-Retamal et al (2013) compared the main characteristics of the carcasses of Chilote lambs feed on naturalized pasture or natural rangeland and did not find differences resulting from the grassland types used by small-scale producers in Chiloe Island, Chile.…”
Section: Quality Of the Ovine Carcassmentioning
confidence: 99%